Mitochondrial Displacement Loop Region SNPs Modify Sjögren’s Syndrome Development by Regulating Cytokines Expression in Female Patients - Zhao, Yufei; Peng, Chenxing; Zhang, Jingjing; Lai, Ruixue; Zhang, Xiaoyun; Guo, Zhanjun (Frontiers in Genetics, 2022)
Mitochondrial dysfunction could induce innate immune response with cytokines releasing to initiate Sjögren's syndrome (SS) onset. Single nucleotide polymorphisms (SNPs) in the mitochondrial displacement loop (D-loop) and mitochondrial DNA (mtDNA) copy number of female SS patients were evaluated for their association with SS in female patients. At the nucleotide site of 152, 16304, 16311 and 16362 in the D-loop, the frequencies for the minor alleles of 152C (p=0.040, odds ratio [OR]=0.504) , 16304C (p=0.045, OR=0.406) , 16311C (p=0.045, OR=0.406) and 16362C (p=0.028, OR=0.519) were significantly higher in the SS patients than those in the female controls, which indicated that 152C, 16304C, 16311C, and 16362C allele in the D-loop of mtDNA were associated with the risk of SS. Meanwhile, the excessive SNPs were accumulated in D-loop region of SS patients (8.955±2.028 versus 7.898±1.987, p0.001, 95% confidence interval [CI]: 0.477-1.637) and mtDNA copy number increased in SS patients (1.509±0.836 versus 1.221±0.506, p=0.006, 95% CI: 0.086-0.490) by a case-control analysis. The subsequent analysis showed that SS risk-related allele 16311C was associated with higher IL-2 levels (p=0.010) at significantly statistical level whereas 152C associated with lower IL-10 levels (p=0.058) at a borderline statistical levels. Our findings suggest that mitochondrial D-loop SNPs are predictors for SS risk, it might modify the SS development by regulating cytokine expression.